Effect of different metal powder anti-oxidants on N220 nano carbon containing low carbon MgO-C refractory: An in-depth investigation. Issue 16 (December 2016) - Behera, Satyananda; Sarkar, Ritwik
Abstract: Effect of three different metal powder antioxidants, namely, Al, Si, and Mg was studied on the development of N220 nano carbon containing low carbon MgO-C refractory. The study was also extended to conventional MgO-C refractory compositions with 16% graphite content. All the refractory compositions were processed as per conventional MgO-C refractory manufacturing techniques and were evaluated for physical, mechanical, thermo-mechanical properties, oxidation resistance and static corrosion resistance against steel converter slag. Microstructural developments and in-situ ceramic phase formation in the compositions were also studied. The results show that nano carbon containing low carbon MgO-C refractory compositions have better properties than conventional composition and among the three anti-oxidants, the aluminum metal powder has shown the improved properties.